BUCKLING ANALYSIS OF ISOTROPIC PLATES (AL 2024-T3) AND QUASI-ISOTROPIC PLATES (CARBON/EPOXY T300/5208) - Hartini, Dwi; Noviyanto F, Hendrix; Arifqi M, Muh. Nadlah; E.Nasution, M.Ridlo (Vortex, 2023)
Buckling is a condition where an object is bent due to the application of a compression (compressive) load on the object. Buckling often occurs in thin-walled structures such as plates. This study aims to determine the buckling strength of isotropic and quasi-isotropic plates. The method used is the Finite Element Method (MEH). The isotropic material uses aluminum 2024-T3, while the quasi-isotropic material uses carbon/epoxy T300-5208 with a [0°/90°/45°/-45°]s laminate arrangement. Modeling and analysis using MSC Patran and Nastran software. The buckling analysis results show the critical buckling stress value on the isotropic plate is  and on the quasi-isotropic plate is  and is still within safe limits when viewed from the Buckling Load Factor (BLF) with a value >1.